A proteomic approach to identifying spermatozoa proteins in Indonesian native Madura bulls - Rosyada, Zulfi Nur Amrina; Pardede, Berlin Pandapotan; Kaiin, Ekayanti Mulyawati; Gunawan, Muhammad; Maulana, Tulus; Said, Syahruddin; Tumbelaka, Ligaya I. T. A; Solihin, Dedy Duryadi; Ulum, Mokhamad Fakhrul; Purwantara, Bambang (Frontiers in Veterinary Science, 2023)
Proteins assist sperm mature, transit the female reproductive tract, and recognise sperm oocytes. Indigenous Indonesian bulls, Madura bulls, have not been studied for reproductive proteomics. As local Indonesian beef livestock, Madura cattle assist in achieving food security; hence, their number must be improved. Thus, the identification of molecular proteomics-based bull fertility biomarkers is needed. This study aimed to characterise the sperm fertility function of the superior Madura bull (Bos indicus × Bos Javanicus) spermatozoa proteome. Frozen semen from eight Madura superior bulls (Bos indicus × Bos javanicus) aged 4–8 years was obtained from the artificial insemination centre (AIC) in Singosari and Lembang. Madura superior bulls are those that have passed the bull breeding soundness evaluation. Frozen sperm were thawed and centrifuged at 3000 × g for 30 min. Proteins in sperm were characterised through proteomic analysis using liquid chromatography–tandem mass spectrometry (LC–MS/MS). The resulting gene symbols for each protein were then subjected to bioinformatics tools, including UniProt, DAVID, and STRING databases. Regarding sperm fertility, the analysis revealed that 15 proteins were identified in the sperm of Madura bulls. Amongst the identified proteins, the superior Madura bull sperm contained several motilities, energy-related proteins, and chaperone proteins. A substantial portion of characterised proteins are linked to metabolic pathways and the tricarboxylic acid (TCA) cycle, contributing to sperm energy production. In conclusion, the first in-depth proteome identification of sperm related to sperm quality and bull fertility of a unique indigenous Madura breed of Indonesia was performed using the LC–MS/MS proteomic method. These findings may serve as a reference point for further studies related to the functions of bovine sperm and biomarkers of fertility and sperm quality.